2014
DOI: 10.5152/tftrd.2014.59354
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Leg Dominance on Single-Leg Stance Performance During Dynamic Conditions: An Investigation into the Validity of Symmetry Hypothesis for Dynamic Postural Control in Healthy Individuals

Abstract: Objective: The primary purpose of the present study was to examine differences in balance performance between the dominant and nondominant legs during dynamic balance tasks in healthy individuals with no regular exercise backgrounds. As a secondary purpose, gender differences in single-leg stance were also investigated. Material and Methods: Twenty-one men and 24 women participated in this study. Single-leg balance performance was evaluated by the Biodex Stability System SD. All subjects were tested at level 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Concerning the control group, no significant side-to-side differences between the dominant and non-dominant leg were observed. This is in line with the literature as studies with healthy subjects showed that lower-limb dominance does not influence the balance performance [29,30]. In absolute terms, the controls demonstrated shorter COP lengths and lower oscillations in the bipedal and single-leg stance but this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the control group, no significant side-to-side differences between the dominant and non-dominant leg were observed. This is in line with the literature as studies with healthy subjects showed that lower-limb dominance does not influence the balance performance [29,30]. In absolute terms, the controls demonstrated shorter COP lengths and lower oscillations in the bipedal and single-leg stance but this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…These conclusions were drawn by Ageberg [13], Lin [14] or Barone [15] who performed posturography on two force plates or by comparing COP variables between the dominant and non-dominant leg in static bilateral conditions. However, during single-leg testing, Hoffmann [16] and Greve [17] or Cug et al [18] did not observe any differences in postural balance between the dominant and non-dominant leg in young adults. The aforementioned studies have mentioned that functional leg dominance may play an important role in bilateral postural stability, where, in most individuals, the left leg is the functionally dominant extremity and the right leg the functionally non-dominant extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Each specific state can be described for different manifestations, which are used to change different functions of the physical system (Volery, Singh, de Bruin, List, Jaeggi, & Baur, 2017;McKeon & Hertel, 2008). Observed, interpreting the basic physical laws of physical activity, regulate the organs of the body, preventing the weathered, it is possible to achieve the possibility of restoring the vertical work established on the central nervous system (Cuğ, Özdemir, & Ak, 2014;Giboin, Gruber, & Kramer, 2015).…”
Section: Introductionmentioning
confidence: 99%